1993
DOI: 10.3354/meps096217
|View full text |Cite
|
Sign up to set email alerts
|

Total lipid content, and lipid and fatty acid composition of the deep-water prawn Pandulus borealis from Balsfjord, northern Norway: growth and feeding relationships

Abstract: Variations in total lipid content (g of lipid, and as % of wet and dry body weights) of the prawn Pandalus borealis, ranging from eggs to 52 mo old adults, indicate that lipid growth exhibits marked seasonal oscillations while growth in carapace length shows only comparatively weak seasonality. Positive (anabolic) lipid growth occurs from about April to September inclusive (with up to 40 % of dry body weight as lipid), the major production season for both phytoplankton and herbivorous zooplankton. Negative (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 14 publications
5
32
0
Order By: Relevance
“…Thus, the enhanced levels of 18:1(n-7) fatty acid in decapods suggest that it was of dietary origin rather than a species-specific marker fatty acid. This conclusion is also supported by the comparison with the fatty acid composition of Pandalus borealis from the north Norwegian Balsfjorden (Hopkins et al 1993), in which only low levels of 18:1(n-7) were found.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, the enhanced levels of 18:1(n-7) fatty acid in decapods suggest that it was of dietary origin rather than a species-specific marker fatty acid. This conclusion is also supported by the comparison with the fatty acid composition of Pandalus borealis from the north Norwegian Balsfjorden (Hopkins et al 1993), in which only low levels of 18:1(n-7) were found.…”
Section: Discussionsupporting
confidence: 64%
“…Due to its commercial importance, extensive lipid investigations have been performed on P. borealis from the north Norwegian Balsfjord (Hopkins et al 1993) and off the south coast of Nova Scotia (Ackman and Eaton 1967). Additionally, lipids of three sea star species from the Balsfjord were studied (Sargent et al 1983), as well as fatty acids in species from a shallow-water hydrothermal habitat off the Kurile Islands (Kharlamenko et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Shrimp are an important link between the benthic and higher trophic levels (Shumway et al 1985), and the documentation of the shift in FAs between shrimp collected at farming locations compared with reference locations has provided a greater insight into the effect of fish farming on the local benthic food web. The general FA profile of the reference shrimp in these investigations resembled the profiles reported earlier by Ackman & Eaton (1967) and Hopkins et al (1993). The FA composition in shrimp and the changes that occurred when experimentally influenced by farm-originated matter was thoroughly described by Olsen et al (2009).…”
Section: Discussionsupporting
confidence: 70%
“…Although a similar trend of FA composition and depletion has been found in the present study, some small differences were encountered. Intraspecific differences have been attributed to female feeding ecology (Biesiot & Perry 1995), nutritional and physiological condition (Amsler & George 1984, Hopkins et al 1993, Wehrtmann & Kattner 1998, differential demands on resource allocation (Jaeckle 1995), and geographic and seasonal variations in embryonic development (Wehrtmann & Kattner 1998).…”
Section: Discussionmentioning
confidence: 99%